Extraction and measurement of urinary tetranor-PGDM in disposable diapers - Nagisa Ito; Tatsuro Nakamura; Naoaki Sakamoto; Akane Hayashi; Takahisa Murata (Elsevier, 2021)
Urinary tetranor-PGDM is a useful diagnostic biomarker for food allergy which often affects infants. We attempted to extract and measure urinary tetranor-PGDM absorbed in polymer of diapers. We applied CaCl2 to the collected polymer, determined the adequate time length of shaking the polymer to release urine, and measured tetranor-PGDM in the extracted urine. This procedure provided high linearity and recovery rate in tetranor-PGDM measurement. We also found that urinary tetranor-PGDM was stable for 24 h at 4°C in diapers. This method can be useful to monitor the food allergic condition of non-toilet trained children.